Temporal Trends in the Risk Profile of Patients Undergoing Outpatient Percutaneous Coronary Intervention: A Report from the National Cardiovascular Data Registry's CathPCI Registry. (March 2016) - Vora, Amit N.; Dai, Dadi; Gurm, Hitinder; Amin, Amit P.; Messenger, John C.; Mahmud, Ehtisham; Mauri, Laura; Wang, Tracy Y.; Roe, Matthew T.; Curtis, Jeptha; Patel, Manesh R.; Dauerman, Harold L.; et al.
Abstract : Background—: Because of recent changes in criteria for coverage for inpatient hospital stays, most nonacute percutaneous coronary intervention (PCI) procedures are reimbursed on an outpatient basis regardless of underlying patient risk. Downstream effects of these changes on the risk profile of patients undergoing outpatient PCI have not been evaluated. Methods and Results—: Using the American College of Cardiology National Cardiovascular Data Registry's CathPCI Registry, we assessed temporal trends in risk profiles and rates of hospital admission among 999 279 patients undergoing PCI qualifying for outpatient reimbursement. We estimated mortality and bleeding risk using validated models from the registry. From 2009 to 2014, the proportion of outpatients not admitted to a hospital after PCI increased from 32.8% to 66.3% ( P <0.001). Patients who were admitted after PCI were older, had greater comorbidities, and experienced more post-PCI complications (all P <0.001). Among those not admitted, the proportion of patients at high risk for predicted mortality increased significantly from 17.0% to 19.8% during the study period ( P <0.001). In contrast, 16.7% of patients admitted after PCI were at low risk for mortality. Conclusions—: Among patients undergoing PCI procedures that qualify for outpatient reimbursement, there has been a temporal decrease in postprocedure hospital admission. Concomitantly, the proportion of these outpatients at high risk for mortality has significantly increased over time. These data suggest that current reimbursement classification could be improved by incorporating patient risk to appropriately match the necessary resources to the needed level of care. Abstract : Supplemental Digital Content is available in the text.